Electron fluence determination per Monitor Unit of a linear accelerator used for radiation therapy - Makridou, A.; Tziaka, C.; Fragopoulou, M.; Stoulos, S.; Zamani, M. (HNPS Advances in Nuclear Physics, 2019)
About 20% of patients in Greece undergoing radiotherapy were irradiated by electron beams with energies ranged between 4 to 20 MeV. The correct determination of electron beam, leads to the proper treatment planning. In this study electron fluence at the isocenter was determined for a linear accelerator ELECTA SL 20 for nominal electron energy of 20 MeV. Two methods have been applied using (a) an ionization chamber in the frame of monthly quality assurance and activation detector (238U). The experimental estimated electron flux, which was in good agreement with the applied calculations using the data of irradiation procedure, ranged between 3.5 up to 4.3 x 108 electrons per cm 2 per sec or 6.1 ±0.7 x 10^7 e.cm-2 per MU.